Manipulasi Lingkungan Menggunakan Cahaya Led (Light Emiting Diode) serta Pemberian Pakan β-karoten untuk Meningkatkan Intensitas Warna Ikan Guppy (Poecilia reticulata) - Sabil, Shahrul Rajab; Thaib, Azwar; maulidya, Rulita; Uliyana, Uliyana; Handayani, Lia (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Freshwater ornamental fish such as guppies (Poecilia reticulata) are popular due to the variety and vibrancy of their body coloration. However, one of the main challenges in their cultivation is the decline in color quality caused by pigment loss, which reduces their visual appeal. Lighting, particularly from artificial sources such as LED lamps, plays a critical role in influencing chromatophore activity involved in pigmentation. The appropriate spectrum, intensity, and duration of light exposure can enhance the brightness and clarity of fish coloration. Additionally, β-carotene, a precursor of carotenoid pigments, is essential for color enhancement. Oil palm (Elaeis guineensis), especially its mesocarp, is a rich natural source of β-carotene and has potential as a natural feed additive. This study aimed to evaluate the effect of combining LED light spectra with β-carotene extract from oil palm mesocarp on color intensity and reproductive performance of guppies. The experiment used a Completely Randomized Design (CRD) with four treatments and two replications: A (red LED + 20% β-carotene), B (yellow LED + 20% β-carotene), C (white LED + 20% β-carotene), and D (no LED + 20% β-carotene). The results showed that treatment C (white LED + 20% β-carotene) produced the best outcomes, with an increase in color score of 28.83 points (measured using Toca Color Finder) and an average of 45 offspring. These findings indicate that the integration of LED lighting and dietary β-carotene derived from oil palm is effective in enhancing both coloration and reproductive performance in guppies